Glucokinase regulatory protein: a balancing act between glucose and lipid metabolism in NAFLD - Zhang, Ziqi; Ji, Guang; Li, Meng (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a common liver disease worldwide, affected by both genetics and environment. Type 2 diabetes (T2D) stands as an independent environmental risk factor that precipitates the onset of hepatic steatosis and accelerates its progression to severe stages of liver damage. Furthermore, the coexistence of T2D and NAFLD magnifies the risk of cardiovascular disease synergistically. However, the association between genetic susceptibility and metabolic risk factors in NAFLD remains incompletely understood. The glucokinase regulator gene (GCKR), responsible for encoding the glucokinase regulatory protein (GKRP), acts as a regulator and protector of the glucosemetabolizing enzyme glucokinase (GK) in the liver. Two common variants (rs1260326 and rs780094) within the GCKR gene have been associated with a lower risk for T2D but a higher risk for NAFLD. Recent studies underscore that T2D presence significantly amplifies the effect of the GCKR gene, thereby increasing the risk of NASH and fibrosis in NAFLD patients. In this review, we focus on the critical roles of GKRP in T2D and NAFLD, drawing upon insights from genetic and biological studies. Notably, prior attempts at drug development targeting GK with glucokinase activators (GKAs) and GKRP with GK-GKRP disruptors have shown potential risks of augmented plasma triglycerides or NAFLD. Conversely, overexpression of GKRP in diabetic rats improved glucose tolerance without causing NAFLD, suggesting the crucial regulatory role of GKRP in maintaining hepatic glucose and lipid metabolism balance. Collectively, this review sheds new light on the complex interaction between genes and environment in NAFLD, focusing on the GCKR gene. By integrating evidence from genetics, biology, and drug development, we reassess the therapeutic potential of targeting GK or GKRP for metabolic disease treatment. Emerging evidence suggests that selectively activating GK or enhancing GK-GKRP binding may represent a holistic strategy for restoring glucose and lipid metabolic balance.